Preliminary radiological survey on high rare-earth containing area in San Vicente, Philippines [Research note] - Iwaoka, Kazuki; Kanda, Reiko; Feliciano, Chitho P.; Tokonami, Shinji; Enriquez, Eliza B.; Hosoda, Masahiro; Dela Cruz, Fe M.; Mendoza, Christopher O.; Palad, Lorna Jean H. (2019)
Erawan Beach area in San Vicente, Palawan Island, Philippines contains rare-earth elements and natural radioactive nuclides at high levels. If the development of mineral resources starts, environmental impacts will be a significant concern for residents in the area. In this study, a preliminary radiological survey on ambient dose equivalent rate and dust concentration was performed in the Erawan Beach area. The ambient dose equivalent rates in each site ranged from 0.060 to 0.81 µSv h−1. External gamma radiation exposures estimated from these values were lower than the reference level range (1−20 mSv y−1) for abnormally high levels of natural background radiation described in the ICRP Publication 103. The dust concentrations in each site ranged from 0.40 to 0.76 mg m−3, which were relatively higher than the typical dust concentration in air (0.05 mg m−3). Based on estimation from the results of the ambient dose equivalent rates and dust concentrations, inhalation radiation exposure due to natural radioactive nuclides in dust will likely be less than external gamma radiation exposure. (Author's abstract)
Includes bibliographical references (pages 501-502)
Keywords: Engineering; Dose rate; High-level environmental radiation areas; Natural radioactive nuclides